Dual functional novel catalytic Cu1−xZrxFe2O4 (x=0, 0.5, 1) nanoparticles for synthesis of polysubstituted pyridines and sunlight‐driven degradation of methylene blue. (23rd August 2018) - Singh, Harminder; Rajput, Jaspreet Kaur; Govil, Garima; Arora, Priya; Badhan, Jigyasa
Abstract : The effect of varied zirconium content on the structural, morphological, magnetic, optical, thermal and catalytic properties of nanoparticles of the ferrite Cu1 − x Zr x Fe2 O4 ( x = 0, 0.5, 1) was investigated. The mixed ferrite was synthesized by the auto‐combustion method using nitrates of respective metals and citric acid as a chelating agent. The as‐prepared nanoparticles showed dual benefits. They were employed as a heterogeneous catalyst for one‐pot synthesis of polysubstituted pyridine derivatives as well as for catalytic degradation of industrial waste dyes such as methylene blue (MB). The highlight of the research reported is the catalytic degradation of industrial waste (MB) with high efficiency in eluent of a wide range of pH (3–13). The proposed nanoparticles arguably offer certain great advantages that include: low cost, facile nature, anti‐leaching property, magnetic recoverability and recyclability. The characterization of the as‐synthesized nanoparticles was done using various techniques. The leaching study was carried out using inductively coupled plasma optical emission spectroscopy. The formation of organic products was confirmed using Fourier transform infrared and 1 H NMR spectroscopies and examination of degradation products of MB dye was carried out using mass spectrometry and UV–visible spectroscopy. Abstract : A novel Cu1− x Zr x Fe2 O4 nanoparticles were synthesized by auto‐combustion technique. Further they have shown excellent activity as a heterogeneous catalyst for the formation of polysubstituted pyridine with 74‐96% yield in 2‐40 minutes and degradation of methylene blue (M.B) with 97.83% in 60 minutes.